Women in politics and government - Lanser, Amanda (Minneapolis, Minnesota : Essential Library, an imprint of Abdo Publishing, 2017)
"Women have made a difference in every field imaginable, and they continue to do so today. Women's Lives in History introduces readers to dozens of these remarkable people. Women in Politics and Government features groundbreaking activists, senators, judges, prime ministers, and many other political figures. Compelling text and vivid photographs bring these women to life."--Publisher's website.
Breaking ground -- Setting the stage for change -- Making waves in Court and Congress -- Women rising -- Women in political mainstream -- New millennium, new milestones -- Facing challenges -- Breaking glass ceilings.
Includes bibliographical references (pages 104-109) and index.
Keywords: Women in public life -- Juvenile literature; Women -- Political activity -- Juvenile literature; Women in public life; Women -- Political activity; Juvenile works